2017
DOI: 10.3389/fnbeh.2017.00018
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect of Social Isolation and High Dose Corticosteroid on Neurogenesis and Emotional Behavior

Abstract: Hypercortisolemia is one of the clinical features found in depressed patients. This clinical feature has been mimicked in animal studies via application of exogenous corticosterone (CORT). Previous studies suggested that CORT can induce behavioral disturbance in anxious-depressive like behavior, which is associated with suppressed neurogenesis. Hippocampal neurogenesis plays an important role in adult cognitive and behavioral regulation. Its suppression may thus lead to neuropsychiatric disorders. Similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…According to the neurogenesis hypothesis of depression, the disturbance of mood and emotion is linked to the impairment of neurogenesis, and restoration of neurogenesis would be a critical factor for the remission from the disease [ 2 , 46 , 47 , 48 ]. If neurogenesis is suppressed, the beneficial effects of antidepressants would be abolished, which may indicate that reversing neurogenesis deficits is a potential therapeutic target of depression [ 49 ].…”
Section: Melatonin and Depressionmentioning
confidence: 99%
“…According to the neurogenesis hypothesis of depression, the disturbance of mood and emotion is linked to the impairment of neurogenesis, and restoration of neurogenesis would be a critical factor for the remission from the disease [ 2 , 46 , 47 , 48 ]. If neurogenesis is suppressed, the beneficial effects of antidepressants would be abolished, which may indicate that reversing neurogenesis deficits is a potential therapeutic target of depression [ 49 ].…”
Section: Melatonin and Depressionmentioning
confidence: 99%
“…Chronic stress has long been associated with the development of depression, one of the major psychiatric disorders worldwide. Depressed patients are usually accompanied by dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis (Chan et al, 2017), mood disturbance, sleep abnormalities (Nollet et al, 2012), anhedonia, and anxiety (Micheli, Ceccarelli, D'Andrea, & Tirone, 2018). Moreover, clinical studies showed a reduction of hippocampal volume, and the atrophy of the hippocampus and prefrontal cortex in patients with depression (Banasr, Dwyer, & Duman, 2011; Micheli et al, 2018; Toda, Parylak, Linker, & Gage, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The same effect was not observed in non-predisposed Wistar rats, suggesting that predisposition to the effects of stress is a determining factor for behavior despair following SIS ( Zanier-Gomes et al, 2015 ). Moreover, several reports also revealed that SIS significantly increased the immobility time of NMRI and C57BL/6J mice or Sprague-Dawley rats submitted to the FST ( Chan et al, 2017 ; Cho et al, 2017 ; Dávila-Hernández et al, 2018 ; Haj-Mirzaian et al, 2015 , Haj-Mirzaian et al, 2019 ). The discrepancies of our results in the behavior despair test, compared to the literature data, could be due to several factors, including biological factors such as strain, age, body weight, gender, and individual differences between animals.…”
Section: Discussionmentioning
confidence: 92%